Effect of Season on the Hatchability of Duck Eggs - Chowdhury, M.M.I.; Ashraf, A.; Mondal, S.P.; Mondol, Newaz Md. Abu Al Moin; Hasan, M.M. (International Journal of Poultry Science, 2004)
This study was conducted in Regional Duck Breeding Farm, Daulatpur, Khulna, Bangladesh with a view to know the seasonal effect on the hatchability of duck eggs. The number of eggs set in the incubator and the number of eggs hatched was used to determine the hatchability percentage. Duck breeding farm practiced artificial incubation for hatching eggs. Data were collected from the record registers of the farm covering the year 1995 to 2002 and 5199928 eggs were set in incubator from 2789000 ducklings were hatched during the period. Data were analyzed using MSTAT-C Statistical Package Program. The result revealed that hatchability of duck eggs were highest in January (59.54%) and lowest in July (48.27%) in case of month wise hatchability whereas winter (57.676%) shows the highest followed by summer (54.135%) and monsoon or rainy season (49.134%). Least-square Analysis of Variance showed that both season and individual months had significant effects on the hatchability of duck eggs. Therefore, it can be concluded that both individual month and season influenced the hatchability of duck eggs.